Public Awareness, Perception, and Knowledge of Bed Bug Infestation Prevalence in Iraq - Hussein Ali Baqir; Wei-Jun Li; Jian-Guo Wang; Song Quan-Ong; Abdul Hafiz Ab Majid (Tehran University of Medical Sciences, 2024)
Background: Bed bugs are blood-feeding insects and are an important urban pest. Bed bugs are nocturnal insects and hide in cracks in walls and beds during the day. The study aims to: (1) determine the bed bugs species that infest Iraq, their infestation source, and their distribution; (2) determine the level of awareness and concern regarding bed bugs among the Iraqi community. Methods: Between 2020 and 2021, a survey of bed bug infestation dynamics was conducted in 18 infested sites located in major cities across eight governorates. The 23-item online survey was distributed over social media to Iraqi citizens between June and July 2022 to survey on their familiarity with bed bug habitat, medical significance, transmission, prevention, control measures, and concerns. Results: There were a total of 1104 bed bugs collected. Based on the morphological characteristics, bed bugs collected from eight Iraqi governorates are identified as Cimex hemipterus. Besides, a high rate of bed bug infestation was observed in workers' dormitories. The online questionnaire was answered by 1843 respondents and based on the feedback, most respondents (55.3%) have no awareness of bed bug infestations, while around 43.8% are somewhat concerned about bed bug infestations in Iraq. Conclusion: Only tropical bed bugs, C. hemipterus were found in all sampled sites. Bed bug infestations are mainly caused by migrant workers and the reuse of second-hand furniture and clothing. The results suggest that the Iraqi government should organize more proper demonstrations on bed bug awareness for the public.